(x-6)(x-5)=(x+7)(x+7)

Simple and best practice solution for (x-6)(x-5)=(x+7)(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-6)(x-5)=(x+7)(x+7) equation:


Simplifying
(x + -6)(x + -5) = (x + 7)(x + 7)

Reorder the terms:
(-6 + x)(x + -5) = (x + 7)(x + 7)

Reorder the terms:
(-6 + x)(-5 + x) = (x + 7)(x + 7)

Multiply (-6 + x) * (-5 + x)
(-6(-5 + x) + x(-5 + x)) = (x + 7)(x + 7)
((-5 * -6 + x * -6) + x(-5 + x)) = (x + 7)(x + 7)
((30 + -6x) + x(-5 + x)) = (x + 7)(x + 7)
(30 + -6x + (-5 * x + x * x)) = (x + 7)(x + 7)
(30 + -6x + (-5x + x2)) = (x + 7)(x + 7)

Combine like terms: -6x + -5x = -11x
(30 + -11x + x2) = (x + 7)(x + 7)

Reorder the terms:
30 + -11x + x2 = (7 + x)(x + 7)

Reorder the terms:
30 + -11x + x2 = (7 + x)(7 + x)

Multiply (7 + x) * (7 + x)
30 + -11x + x2 = (7(7 + x) + x(7 + x))
30 + -11x + x2 = ((7 * 7 + x * 7) + x(7 + x))
30 + -11x + x2 = ((49 + 7x) + x(7 + x))
30 + -11x + x2 = (49 + 7x + (7 * x + x * x))
30 + -11x + x2 = (49 + 7x + (7x + x2))

Combine like terms: 7x + 7x = 14x
30 + -11x + x2 = (49 + 14x + x2)

Add '-1x2' to each side of the equation.
30 + -11x + x2 + -1x2 = 49 + 14x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
30 + -11x + 0 = 49 + 14x + x2 + -1x2
30 + -11x = 49 + 14x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
30 + -11x = 49 + 14x + 0
30 + -11x = 49 + 14x

Solving
30 + -11x = 49 + 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
30 + -11x + -14x = 49 + 14x + -14x

Combine like terms: -11x + -14x = -25x
30 + -25x = 49 + 14x + -14x

Combine like terms: 14x + -14x = 0
30 + -25x = 49 + 0
30 + -25x = 49

Add '-30' to each side of the equation.
30 + -30 + -25x = 49 + -30

Combine like terms: 30 + -30 = 0
0 + -25x = 49 + -30
-25x = 49 + -30

Combine like terms: 49 + -30 = 19
-25x = 19

Divide each side by '-25'.
x = -0.76

Simplifying
x = -0.76

See similar equations:

| 10.6x+95.68=-9.4x+93.94 | | 5(7q+9)+3= | | 36x^2+72x=0 | | y=x^4+3x^2+1 | | 8y=-9x+3 | | 3(i+2)=4i | | 4y-9+y+20=6y+20-4y | | 14x-4x+x+4x=30 | | 1.125=G-4.4 | | 1/4x-5=3/4x-12 | | 5/6x=1/2 | | 12x^3+36x^2=0 | | 2=b*13 | | -2(4)+4y=16 | | -2(2)+4y=16 | | 3(h-3)-2=2(h-5) | | x+x-2x=14 | | -2x+6=-2(3x+7) | | 4.1-Y=2.3 | | -4(2)+5y=8 | | 1.30y=50 | | p-2(p-15)=9p | | y+4/5=3y+1/5 | | y=50-2x | | 2x=24-4x-2x | | 2/3(18x-15y)-3/4(16x-36y) | | 9/6=81/b | | (86-6x)/8 | | -4(5t-5)+9t=3t-5 | | -2(-2x-6)=4x | | 3/4x4 | | 550b+175000=220650 |

Equations solver categories